Performance optimization of sulfur dioxide (So2) desulfurization by oil palm-based activated carbon using box-behnken design - Sooriyan, S. K.; Ibrahim, N.; Hanif, M. A.; Hasan, M.; Abdullah, S.; Adriansyah, A. A.; Setianto, B.; Syafiuddin, A. (AMG Transcend Association, 2022)
Sulfur dioxide (SO2) emission into the atmosphere brought by the burning of fossil fuels in the industries posed significant negative effects on the environment and human beings. Adsorption using activated carbon from agricultural wastes is a viable method commonly used to counter this major problem. SO2 breakthrough experiment was conducted on a fixed bed reactor using oil palm empty fruit bunch activated carbon. The sorbent utilized in this study was characterized via N2 adsorption-desorption isotherm, field emission scanning electron microscopy, and Fourier transform infrared spectroscopy. Three parameters, i.e., reaction temperature, inlet SO2 concentration, and adsorbent dosage, were optimized using Box-Behnken Design. The highest SO2 removal was obtained at 70 °C, 2000 ppm of SO2, and 1 g of adsorbent with adsorption capacity of approximately 1101 mg SO2 /g activated carbon. The developed model was validated using Analysis of Variance (ANOVA), and good agreement between predicted and actual values was obtained. Inlet SO2 concentration, adsorbent dosage, the interaction between these two parameters, and all quadratic terms were found to be significant factors, with adsorbent dosage being most significant based on its highest F-value.